2000
DOI: 10.1046/j.1365-2826.2000.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential In Vitro Secretion of Gonadotropin‐Releasing Hormone (GnRH) and [Hydroxyproline9]GnRH from the Rat Hypothalamus During Postnatal Development

Abstract: The differential secretion of gonadotropin-releasing hormone (GnRH) and [hydroxyproline9]GnRH (HypGnRH) has been recently reported from the adult rat hypothalamus. We report here in vitro cosecretion of HypGnRH and GnRH by the hypothalamus of 2-45 day-old-rats and provide evidence that they are differentially regulated throughout development. The secretion of both forms of GnRH was increased in a dependent manner during depolarization by high K+ solutions, and was stimulated by forskolin and 12-O-tetradecanoyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Our data confirm that the hypothalamic GnRH-like content increased with advancing age in both sexes, reaching higher amounts in males than in females [38]. This increase was greater in the case of mGnRH than with mHypGnRH, and the relative proportion of mHypGnRH decreased in the developing hypothalamus [34]. The hydroxylated and non-hydroxylated forms of [Gly 11 ] precursors and their respective processed peptides (free-acid and native decapeptides) detected were used to examine the biosynthetic pathway of mGnRH and mHypGnRH by comparing [Gly 11 ] precursor to processed peptide molar ratios between hydroxylated and non-hydroxylated molecules.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our data confirm that the hypothalamic GnRH-like content increased with advancing age in both sexes, reaching higher amounts in males than in females [38]. This increase was greater in the case of mGnRH than with mHypGnRH, and the relative proportion of mHypGnRH decreased in the developing hypothalamus [34]. The hydroxylated and non-hydroxylated forms of [Gly 11 ] precursors and their respective processed peptides (free-acid and native decapeptides) detected were used to examine the biosynthetic pathway of mGnRH and mHypGnRH by comparing [Gly 11 ] precursor to processed peptide molar ratios between hydroxylated and non-hydroxylated molecules.…”
Section: Discussionsupporting
confidence: 83%
“…But, in addition to a previous study [34], we established here that both decapeptides are present at an early developmental stage in association with some of their catabolites and precursors which have been already identified in the adult animals [15, 16] and in the GT1 cell line [35, 36]. The chromatography of large amounts of tissues and the use of two combined HPLC steps made it possible to detect these additional metabolic compounds which mostly coelute with mHypGnRH or mGnRH on a single RP-HPLC [37].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is reported that [Hyp 9 ]GnRH is released from the hypothalamus by different mechanisms in adult [39]and developing rats [40]and can potentially act on the secretion of human chorionic gonadotropin secretion from perifused placental cells [41]. Nevertheless, its actions are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…178 The physiological significance of (Hyp 9 ) GnRH remains unknown. Gautron and colleagues have shown that as much as 10% of GnRH-like peptide in the hypothalamus exists as (Hyp 9 ) GnRH in adult rats.…”
Section: Gnrh-1 Peptidementioning
confidence: 99%